2010
DOI: 10.1182/blood-2009-08-240044
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of caveolin-1 in adult T-cell leukemia

Abstract: Caveolin-1 is implicated in the regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This finding is attributable to the discovery of multiple fraudulent articles during the course of investigation of a single instance of fraud. For example, the retraction of a 2010 Blood article by Sawada et al (14) was followed in rapid succession by the retraction of 30 additional articles originating from the laboratory of Naoki Mori (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is attributable to the discovery of multiple fraudulent articles during the course of investigation of a single instance of fraud. For example, the retraction of a 2010 Blood article by Sawada et al (14) was followed in rapid succession by the retraction of 30 additional articles originating from the laboratory of Naoki Mori (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…al (2012) observed that Cav-1 is necessary for the transformation of quiescent monocytes to active macrophages. Upregulation of Cav-1 has been observed in adult T-cell leukemia cells (Sawada et al, 2010) and macrophages undergoing apoptosis (Gargalovic and Dory, 2003), and Cav-1 has been shown to play a critical role in induction of inflammatory pathways via interleukin-1β (IL-1β) signaling and NFκB activation (Garrean et al, 2006). In the respiratory system, alveolar macrophages with an inflammatory phenotype were associated with enhanced expression of Cav-1 (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-3 KO mice are viable but subject to skeletal and cardiac myopathies (Monier et al, 1995, Hagiwara et al, 2000), and our laboratory and others have demonstrated a critical role for caveolin in protection from ischemia-reperfusion injury (Bromley et al, 2001, Galbiati et al, 2001, Chidlow and Sessa, 2010, Stary et al, 2012). MLR-mediated signal transduction is an important element in the activation of the immune system (Gargalovic and Dory, 2003, Ohnuma et al, 2004, 2009, Sawada et al, 2010, Fu et al, 2012) and inflammatory response (Oakley et al, 2009, Garrean et al, 2006, Feng et al, 2010, Xu et al, 2010, Hu et al, 2008), however this previous work has largely focused on the more ubiquitously expressed Cav-1 isoform. In contrast, the role of Cav-3 in immune system signaling has been relatively under-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9 Of concern is the discovery of multiple fraudulent cases, committed by the same laboratory or individual, when investigating a single fraud instance. Sawada et al 16 was retracted from the journal, Blood. Consequently, 30 additional articles were retracted originating from the same laboratory.…”
Section: Fraud On the Risementioning
confidence: 99%